Influences of climacteric in female sexual activity - Anthonio Alisancharles Batista de Almeida; Cecília Danielle Bezerra Oliveira; Fabiana Ferraz Queiroga Freitas; Karolliny Abrantes de Sousa; Maria Tibéria da Silva Carolino; Rosimery Cruz de Oliveira Dantas (Universidade Federal do Ceará, 2016)
Objective: to identify complaints of sexual function related to climacteric symptoms among women in climacteric age. Methods: descriptive study. A sample of 330 women aged from 35 to 65 years old, with three previous Pap tests. We used a questionnaire developed by the researchers. A descriptive statistical analysis was performed having the central tendency of proportion and measure the average as a parameter. Results: it was evidenced that 50% were between 35-45 years, 73% were sexually active, 59.4% had decreased libido, and 58.5% reported dyspareunia. Conclusion: it is necessary that the health services and professionals are aware of the influence of climacteric on women's health to develop strategies aimed at quality of life.